2019
DOI: 10.21273/jashs04524-18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fruiting and Biennial Bearing Potential on Spur Quality and Leaf Gas Exchange in Apple

Abstract: Uniform annual apple (Malus ·domestica) fruit production is highly dependent on consistent flower formation from year to year, as inconsistent flowering can lead to the biennial bearing observed in some high-value cultivars. The presence of fruit on a spur has been considered the main cause of the expression of biennial bearing and the inhibition of flower initiation, with a number of theories being introduced to explain the phenomenon. In the current experiment, individual spurs of annual bearing cultivars (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Plants engaged in higher food production with increased leaf area during the pre-flowering phase, whereas higher metabolic activity of plants during the reproduction phase increased the water and energy requirements, which could explain why photosynthetic rate was higher during the pre-flowering phase than the flowering phase. This was in line with results of [8][9][10][11]. Alternate flowering trees exhibited a higher photosynthetic rate than other trees, which was consistent with the findings of [12] in the Apple tree.…”
Section: Photosynthetic Ratesupporting
confidence: 92%
“…Plants engaged in higher food production with increased leaf area during the pre-flowering phase, whereas higher metabolic activity of plants during the reproduction phase increased the water and energy requirements, which could explain why photosynthetic rate was higher during the pre-flowering phase than the flowering phase. This was in line with results of [8][9][10][11]. Alternate flowering trees exhibited a higher photosynthetic rate than other trees, which was consistent with the findings of [12] in the Apple tree.…”
Section: Photosynthetic Ratesupporting
confidence: 92%
“…Scion vigor may also be associated with concentrations or ratios of growth inhibiting to promoting compounds [31] or nutrient acquisition and transport properties of a given rootstock-scion combination [32,33]. Of the three cultivars evaluated, gas exchange of 'Honeycrisp' was similar to Fuji and higher than Gala [34], yet field-grown 'Honeycrisp' trees completed their terminal extension growth by mid-season; terminals of container-produced trees only elongated an additional ~20% after 15-August, which was markedly less than 'Fuji' or 'Gala'. The early seasonal cessation of 'Honeycrisp' terminal growth is a common observation in the orchard and is hastened by the presence of fruit.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of 'Gala' to produce similar canopy growth with significantly less root was not observed for the other cultivars and is illustrated by a smaller difference in the percentage of total plant DMC in roots versus shoots when comparing the two production systems (Figure 2). An alternative index is the ratio of total canopy leaf area (cm 2 ) to total root length (cm) (34). More specifically, the total absorptive root length, since presumably plant investment in leaf area is dependent on the capacity of the ephemeral, absorptive roots to meet its evaporative demand.…”
Section: Discussionmentioning
confidence: 99%
“…Not only are they the main receptor for environmental signals but they also produce carbohydrates and plant growth regulators. Recently, we showed that flowering did not appear to be related to factors associated with spur carbohydrate status, suggesting a direct role of genes regulating flowering and plant growth regulators (Elsysy et al, 2019). Flower induction genes have been shown to be active in the leaves (Hanke et al, 2007).…”
mentioning
confidence: 97%